2021
DOI: 10.2147/ceor.s291463
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophic Health Expenditure among Chronic Patients Attending Dessie Referral Hospital, Northeast Ethiopia

Abstract: Background Catastrophic health expenditure is health spending that is not covered by a health-care plan. These costs tend to escalate over time, due to chronic illnesses. Catastrophic health expenditure leads to decreased use of health services and poorer treatment outcomes. This study measured the extent of and factors associated with catastrophic health expenditure among chronically ill patients attending Dessie Referral Hospital in northeast Ethiopia. Methods An inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…Of these, six articles were conducted at the national level [ 13 , 33 – 37 ]. The remaining 21 articles were conducted in different parts of Ethiopia: i.e., six articles were conducted in the south regional state [ 14 , 33 – 37 ], five articles in Amhara regional state [ 38 42 ], five articles in Addis Ababa city [ 43 47 ], three articles in Oromiya regional state [ 48 – 50 ], one article in Bensangual-Gumuz regional state [ 51 ], and one article in a combination of Afar and Oromiya regional states [ 52 ]. Finally, 17 articles were found to be eligible and included in the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of these, six articles were conducted at the national level [ 13 , 33 – 37 ]. The remaining 21 articles were conducted in different parts of Ethiopia: i.e., six articles were conducted in the south regional state [ 14 , 33 – 37 ], five articles in Amhara regional state [ 38 42 ], five articles in Addis Ababa city [ 43 47 ], three articles in Oromiya regional state [ 48 – 50 ], one article in Bensangual-Gumuz regional state [ 51 ], and one article in a combination of Afar and Oromiya regional states [ 52 ]. Finally, 17 articles were found to be eligible and included in the meta-analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…et.al. (2020) [ 47 ] Addis Ababa Cross-sectional 404 participants 6 Low risk Tsega G. et al (2021) [ 41 ] Amhara Cross-sectional 422 participants 7 Low risk Yohannes S. et al (2021) [ 42 ] Amhara Cross-sectional 302 chronically ill patients 6 Low risk …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are congruent with those of other recent investigations. Shumet et al observed that the most prevalent causes of catastrophic health spending among diabetic patients were high-cost services and medicines [ 31 ]. Other findings have shown that chronic disease-affected families are much more likely to spend on medicines than matched control unaffected families [ 32 ].…”
Section: Discussionmentioning
confidence: 99%